The Application of Cooperative Learning Model during Online Learning in the Pandemic Period - Tiodora Fermiska Silalahi; Ahmad Fakhri Hutauruk (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
In improving the quality of school education and learning in the future, it is necessary to change the mindset that will be used as the basis for implementing a learning program. What's more in the co-19 pandemic period that requires students to be able to study at home without interacting in class for a while. In the past the learning process was conventional, namely face-to-face in class. But even then, most teaching processes are still dominated by teachers. As a result, teaching and learning activities place more emphasis on teaching and not on learning. Learning activities favor the interests of those who teach. Efforts for learning to be focused on students, it is necessary to apply a cooperative learning model which is a form of change in mindset in learning activities at school. However, during this pandemic, the next challenge is how the cooperative process can take place in the online learning process. The absence of a physical meetup becomes an obstacle that can be minimized by the adaptation of the teacher in the distance learning process. In this case the teacher no longer dominates the learning activities, but rather becomes the facilitator and mediator of the process. The cooperative learning model is designed by giving opportunities to students together to build their own knowledge.